MADRASAH: ANTARA TRADISI DAN TUNTUTAN PERUBAHAN - Zaedun Na'im (STAI Ma'had Aly Al-Hikam Malang, 2015)
The situation of progress of development in various sectors of life urged the madrasa to improve the quality of education are developed. The programs intelligently based on contemporary needs, demands to be realized, so that the existence of madrassas can be functional in answering daily reality, both in the context of developing science and technology, create jobs or in an attempt to foster a critical attitude, dynamic and be autonomous Madrasah need to be developed to meet three demands minimal in improving the quality of madrasah, namely: (1) how to make the madrassa as a vehicle for fostering the spirit or practice of Islamic life, (2) how to strengthen the presence of the madrassa so equally with the school system, (3) how the madrassa able to respond to future demands science and technology in order to anticipate future developments and globalisasi Madrasah era in the context of preparing learners face of changing global age, it becomes important role. Madrasah success in preparing students to face future challenges more complex will produce graduates with a competitive advantage and became the leader of the nation's leaders that will determine the direction of the development of this nation